Graphical modelling of linkage disequilibrium - Thomas, Alun (Henry Stewart Talks, 2004)
Describing linkage disequilibrium, Visualisation approaches: triangular grid-plots and LD maps, Graph theory as a useful way of describing complex LD patterns, Software
Archived at 2021/02/25